Postawa osób po laryngektomii całkowitej wobec Nordic Walking = The attitude of people after total laryngectomy to Nordic Walking - Agnieszka Hamerlińska - Latecka (Kazimierz Wielki University, 2016)
Hamerlińska - Latecka Agnieszka. Postawa osób po laryngektomii całkowitej wobec Nordic Walking = The attitude of people after total laryngectomy to Nordic Walking. Journal of Education, Health and Sport. 2016;6(8):852-860. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.213534 http://ojs.ukw.edu.pl/index.php/johs/article/view/4095     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 01.12.2016.       Postawa osób po laryngektomii całkowitej wobec Nordic Walking   The attitude of people after total laryngectomy to Nordic Walking   Agnieszka Hamerlińska - Latecka   Wydział Pedagogiki i Psychologii, Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Słowa kluczowe: laryngektomia całkowita, nordic walking, postawa, rehabilitacja Key words: attitude, nordic walking, rehabilitation, total laryngektomy   Streszczenie Niniejszy artykuł dotyczy postaw osób po laryngektomii całkowitej wobec uprawiania Nordic Walking. Zawiera wyjaśnienie pojęcia postawa, deskrypcję laryngektomii całkowitej wraz z opisem jej konsekwencji. Następnie odnaleźć można opis celów rehabilitacji ruchowej stosowanej u osób laryngektomowanych. Na koniec prezentowane są wyniki badań. Abstract This article is about the attitudes of the total laryngectomy to Nordic Walking. It contains an explanation of the concept of attitude, the total laryngectomy with a description of its consequences. Then one can find a description of the purpose of rehabilitation used in people laryngectomees. At the end of the test results are presented.